2020
DOI: 10.1016/j.ijid.2020.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Management of latent tuberculosis infection in China: Exploring solutions suitable for high-burden countries

Abstract: China is one of the countries with a high burden of tuberculosis (TB) and latent tuberculosis infection (LTBI). It was recently estimated that China had the highest LTBI burden in the world, with approximately 350 million persons living with the infection. The prevalence of LTBI in China is overestimated by tuberculin skin test (TST) as compared to interferon-gamma release assay (IGRA). A population-based study found that IGRA positivity rates ranged between 13.5% and 19.8%. The annual TB infection rate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…and 20% in a population-based study [19]. Due to large size of latent TB population, latent TB treatment is not systemically adopted in national guideline, but restricted to patients with diverse immune de ciencies, such as HIV, silicosis, receiving anti-tumour necrosis factor treatment, receiving dialysis, organ or hematologic transplantation [20,21]. Because of simpler treatment regimen for latent TB compared with active TB, preventive chemotherapy of latent TB may be preferable in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…and 20% in a population-based study [19]. Due to large size of latent TB population, latent TB treatment is not systemically adopted in national guideline, but restricted to patients with diverse immune de ciencies, such as HIV, silicosis, receiving anti-tumour necrosis factor treatment, receiving dialysis, organ or hematologic transplantation [20,21]. Because of simpler treatment regimen for latent TB compared with active TB, preventive chemotherapy of latent TB may be preferable in lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…So, to achieve the second WHO milestone, new measures must be taken. In order to improve the diagnosis [32][33][34][35], treatment [36,37] and TB prevention services [38][39][40], a lot of research have been carried out around the world. A study from Nepal found that active case nding could reduce catastrophic costs [41].…”
Section: Discussionmentioning
confidence: 99%
“…So, to achieve the second WHO milestone, new measures must be taken. In order to improve the diagnosis [27][28][29][30], treatment [31,32] and TB prevention services [33][34][35], a lot of research have been carried out around the world. A study from Nepal found that active case finding could reduce catastrophic costs [36].…”
Section: Discussionmentioning
confidence: 99%